ACI Update ACI News (Journal of Airport Management, 2019)
Purpose of review Cutaneous adverse reactions are among the most frequent complications of anticancer therapies and a major cause of treatment interruption, dose reduction, or switching to alternative regimens. This review explores the complex interplay between direct tissue toxicity and immune-mediated mechanisms underlying chemotherapy-induced skin reactions. Recent findings Emerging evidence indicates that chemotherapy-induced skin reactions arise from dynamic interactions among keratinocyte injury, innate immune activation, cytokine-driven inflammation, and adaptive immune responses, resulting in overlapping clinical phenotypes rather than isolated pathogenic processes. This evolving concept is exemplified by common reactions such as maculopapular eruptions, toxic erythema of chemotherapy, hand-foot syndrome, acneiform rash, and radiation recall dermatitis, as well as by immune-mediated conditions including urticaria, fixed drug eruption, severe cutaneous adverse reactions, bullous pemphigoid, and lichenoid eruptions. The expanding use of targeted therapies and immune checkpoint inhibitors further broadened this spectrum and highlighted the complexity of the underlying mechanisms. Summary Recognizing the complex interplay between tissue toxicity and immune activation provides a more comprehensive framework for interpreting chemotherapy-induced skin reactions. Improved clinical phenotyping, integrated allergologic assessment, and close collaboration between oncologists and allergists are essential to optimize diagnosis, guide rechallenge or desensitization strategies and avoid unnecessary discontinuation of effective anticancer therapies.